Antimicrobial enhancement of Red onion crude extract using Epsilon-polylysine - Phakawan, J.; Tepsorn, R. (International Journal of Agricultural Technology, 2021)
The antimicrobial activities of red onion extract were investigated by using 50% ethanol solution and combination with epsilon-polylysine against 5 strains of foodborne microorganisms. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidial Concentration (MBC) were determined using Macrobroth dilution method against selected test organism including Bacillus cereus, Staphylococcus aureus, Listeria monocytogenes, Salmonella Typhimurium and Escherichia coli O157:H7. The MIC of red onion crude extract (ROE) was ranged from 15.00 to 19.00 % (w/v) and the MBC was ranged from 25.00 to 35.00 % (w/v). For epsilon-polylysine (EPL), the MIC was ranged from 0.0150 to 0.0400 % (w/v) and the MBC was ranged from 0.0300 to 0.0650 % (w/v). In addition, the results from the determination of Fractional Inhibitory Concentration Index (FICindex) of the combination between red onion crude extract and epsilon-polylysine using Checkerboard assay against Bacillus cereus, Staphylococcus aureus, Listeria monocytogenes, Salmonella Typhimurium and Escherichia coli O157:H7 were 0.50, 0.50, 0.50, 0.50 and 0.75, respectively. These FICindex values indicated the synergistic activity. The study on the efficacy of the combination system were also determined by Time Killing analysis without interfering substances. The result indicated that the antimicrobial activity of combination system was depended on the concentration of red crude extract and epsilon-polylysine. Therefore, synergistic effect of red crude extract and epsilon-polylysine potentially enhances their antimicrobial activities and may be used as an alternative natural antimicrobial material for food preservative